A game-theoretical approach on the construction of a novel agri-food supply chain model supported by the government - Hamidoğlu, Ali (Expert systems with applications, 2024)
In this study, a novel government-backed agri-food supply chain model (GBASM) is introduced among farmers and agricultural enterprises in their respective market. In the GBASM, the government provides subsidies to each member of the supply chain to encourage them to collaborate on a common economic platform. A game-theoretic perspective is established among farmers and agricultural enterprises to determine whether or not they should participate in this new model for their economic benefits. In this regard, a Nash game is proposed in which the Nash equilibrium is derived as the mixed equilibrium strategy, assuming that farmers and agricultural enterprises are two rational actors cooperating over market price in the GBASM. In numerical experiments, two sample models are examined based on the parameter values of each participant, and the grey wolf optimizer algorithm is utilized to derive mixed decision-making strategies from a variety of scenarios considered for each sample model. Sensitivity analyses are conducted to assess the impact of the GBASM on the decision-making processes of farmers and agricultural enterprises. The integration of the GBASM into a case study of the tomato supply chain in Buenos Aires, Argentina, confirms the robustness of the model and creates economically feasible and consistent pricing structures within the local area. •A novel government-backed agri-food supply chain model (GBASM) is presented.•A two-player game model is proposed in the GBASM according to pricing.•A Nash game is introduced within the GBASM to promote member co-operation.•Subject of whether chain members must adopt the GBASM is examined numerically.•The GBASM integrates with the tomato supply chain in Argentina for market stability.